Differences in picture naming between children with cochlear implants and children with typical hearing. Issue 12 (December 2021) - Cambra, C.; Losilla, J.M.; Mena, N.; Pérez, E.
Abstract: Increase in the auditory abilities of children with cochlear implants (CIs) has led to an improvement in naming tasks, although divergent results are still being reported; this strongly suggests that further studies are needed. The study aims to compare the responses in a picture-naming activity between the complete population of children aged 5 to 7 with cochlear implants in Catalonia -Spain- (N = 31), without developmental problems, and a matched sample of 31 children with typical hearing. A picture-naming task was used to assess their lexical naming abilities. The results show that children with CIs provide more non-responses, they produce fewer words correctly, they require a longer reaction time and they commit more picture-naming errors than children with typical hearing. The auditory age does significantly affect the results, but not the type of implant. In spite of the hearing gain achieved with the cochlear implant and the listening experience progressively achieved in distinct contexts, further explicit work on lexical naming in speech-therapy intervention is clearly required. Abstract : Picture naming, Cochlear implant, Childhood, Education